Druckfiltration von Kohlenstoffnanoröhren‐Suspensionen. Issue 3 (6th February 2014) - Dresel, Alexander; Teipel, Ulrich; Teipel, Ulrich; Weber, Alfred
<x xml:space="preserve">Abstract</x> Carbon nanotubes (CNTs) are tubular carbon particles that shells are similar structured to graphite and exhibit diameters in the nanometer range (< 100 nm). Besides the suspension, production and modification of these particles require often the recovering and drying of the accruing CNT‐suspensions. Common thermal solid‐liquid separation processes often cause strong particle agglomeration or even damnification of carbon nanotubes. In this work, pressure‐driven filtration processes were investigated and developed for the mechanical solid‐liquid separation of multi‐walled carbon nanotube suspensions.